KAJIAN NORMATIF MENGENAI PENGGUNAAN DISCRECIONARY POWER BAGI PEJABAT PEMERINTAH DALAM UPAYA MENINGKATKAN KUALITAS PENYELENGGARAAN PEMERINTAHAN - Mulyani, Tri; Nuswanto, A Heru; Pujiastuti, Endah (Universitas Semarang, 2017)
Each legal state requires that in the administration of the government should be based on the legality principle of the provisions of the law, including Indonesia. However, in terms of carrying out the duties and obligations of government administration in order to provide and maintain the quality of public services and prosperity, in addition to providing guarantees and protection for citizens, it can not just stick to the principle of legality, because the day, the increasingly complex demands of public services and diverse. Problems after problems arise in the community, and in such conditions the principle that the government should not refuse to provide services to the public on the grounds there is no legislation that regulate it or not / no legislation on which the authority to do legal action . Therefore the government is given free authority to perform actions / deeds without having to be bound by legislation that is discretion. So in this study will be studied more deeply about the importance of the use of discretion for government officials in the administration. The research method used is normative juridical research type, with approach of legislation and concepts, analytical descriptive specification, data collection with literature study and will be analyzed qualitatively. The results of the study indicate that the importance of discretionary power for government officials in the administration is an alternative to fill the shortcomings and weaknesses in the application of legality principle (wetmatigheid van bestuur), so that in addition to the government can protect and ensure legal certainty of citizens, the government can also provide public services and welfare for citizens.